The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1002/ajmg.a.32239
|View full text |Cite
|
Sign up to set email alerts
|

Cohen syndrome resulting from a novel large intragenic COH1 deletion segregating in an isolated Greek island population

Abstract: Cohen syndrome, caused by mutations in the COH1 gene, is an autosomal recessive disorder consisting of mental retardation, microcephaly, growth delay, severe myopia, progressive chorioretinal dystrophy, facial anomalies, slender limbs with narrow hands and feet, tapered fingers, short stature, kyphosis and/or scoliosis, pectus carinatum, joint hypermobility, pes calcaneovalgus, and, variably, truncal obesity. Here, we describe the clinical and molecular findings in 14 patients from an isolated Greek island pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 14 publications
2
39
0
3
Order By: Relevance
“…10 In four patients from three families, MLPA identified a COH1 large deletion sharing the same extent with one previously reported in an isolated Greek Island population, spanning from exons 6 to 16. 16 In our patients, the deletion was heterozygous in two families and homozygous in an apparently non-consanguineous family. 10 Interestingly, this latter patient displays the same constellation of facial features reported in Greek patients with homozygous deletion including thick hair with low hairline, strabism, lack of nasofrontal angle, short upturned philtrum and prominent maxillary central incisors (patient 5, Figure 1).…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…10 In four patients from three families, MLPA identified a COH1 large deletion sharing the same extent with one previously reported in an isolated Greek Island population, spanning from exons 6 to 16. 16 In our patients, the deletion was heterozygous in two families and homozygous in an apparently non-consanguineous family. 10 Interestingly, this latter patient displays the same constellation of facial features reported in Greek patients with homozygous deletion including thick hair with low hairline, strabism, lack of nasofrontal angle, short upturned philtrum and prominent maxillary central incisors (patient 5, Figure 1).…”
Section: Discussionmentioning
confidence: 51%
“…10 Copy number changes in COH1 have been previously investigated in patients with Cohen syndrome by qPCR using probes designed on a 1 2 3 3 4 5 7 8 9 10 11 12 13 15 16 16 17 17 18 19 20 21 22 23 24 24 25 26 27 28 29 30 31 31 32 33 34 34 35 35 36 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 limited number of exons. 10,16 Only recently, a targeted oligonucleotide array with a median resolution of 200 bp was designed within the gene, which considerably increased the mutation detection rate. 11 Using this technique, the authors identified COH1 large deletions in nine patients from seven families, showing that they represent an important cause of Cohen syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Se han descrito mutaciones puntuales, deleciones y duplicaciones del locus 8q22-q23 que incluyen este gen y se traducen en alteraciones de una proteína transmembranal de función desconocida (1). El fenotipo característico consiste en discapacidad intelectual, microcefalia, facies característica, anormalidades oftálmicas, obesidad central e hipotonía (2,3).…”
Section: Introductionunclassified